Pengenalan Peluang Pendapatan dari Usaha Pengolahan KOLING (Kolang Kaling) menjadi Produk Siap dipasarkan pada Desa Cawang Lama Kecamatan Selupu Rejang - Novianti, Maya; Syafitri, Twenty Mariza; Sultanah, Nabila Dhia Rahmah (Jurnal Dehasen Mengabdi, 2023)
Currently, people are required to be able to innovate products, not just focusing on the utilization of agricultural products. The people in the village are expected to be able to produce a product from existing agricultural products. So that income that can be received is not only from agricultural products but from a product that is ready to be sold. In the village of Cawang Lama, Selupu Rejang sub-district, there are village people who work odd jobs to produce kolang-kaling fruit because the location has many palm or aren palm trees, in which palm or aren trees produce a lot of kolang-kaling fruit. The purpose of this community service is to be able to help provide ideas in producing a product that is ready to be sold, namely Koling (Kolang Kaling) Juice with various flavors, there is also a calculation regarding the amount of capital, selling price and amount of profit. So that the village community can understand the income opportunities that can be obtained.